Factors that lead to happiness at the workplace among academicians: a case of UiTM / Munira Amirullah - Amirullah, Munira (Faculty of Business and Management, 2017)
There is the way in order to know the factors that lead to happiness at the workplace as it is one of the important determinants to make people happy with their environment. In this study, it is to determine the factor that lead to happiness at the workplace among academicians in selected organization. Through this study, it is covered a sample of 70 respondents out of 84 population of academicians from Business Management Faculty in Universiti Teknologi Mara Kampus Bandaraya Melaka. The sample that have been selected through convinient technique as the primary data was collected by using questionnaires. The data analysis that have been used in this study are Pearson Correlation analysis and also Multiple Regression analysis. From the result in Pearson Correlation analysis, all the independent variables, employment status, income, friendship and work activities are significantly related to happiness at the workplace. On the other hand, work activities is the most variable that related to happiness at the workplace. Finally, from the result that have been obtained in regression model, the most important independent variable was work activities as it had highest Beta value of 0.399. The study have found out that these factors affect happiness at the workplace among the academicians in UiTM Kampus Bandaraya Melaka as all the independent variables and dependent variable move in the same direction. Thus, it indicates that strong factors that can give big impact towards happiness at the workplace among academicians.